TRANSMISSION DYNAMICS OF EBOLA VIRUS DISEASE WITH VACCINE, CONDOM USE, QUARANTINE, ISOLATION AND TREATMENT DRUG: Transmission dynamics of Ebola virus disease - Ojoma, Ahman Queeneth; David, Omale; Chukwuma, Asogwa Christopher; Ugochukwu, Nnaji Daniel; Christopher Ezike, Mbah Godwin (African Journal of Infectious Diseases (AJID), 2022)
Background: Ebola Virus Disease (EVD) has brought the human population, especially the West African race, great losses in so many areas such as economic productivity and human life. During the 2014 Ebola Virus outbreak, the disease devastated and threatened the whole world. EVD symptoms (fever, diarrhea, vomiting, etc) may appear anywhere between two to twenty-one days after infection. Those that recovered from the disease return to being susceptible again and can transmit the virus through semen as research has shown the virus presence in semen even after recovery. Material and Methods: Mathematical modeling method with the combination of vaccine, condom use, quarantine, isolation and treatment drug together as control measures in a population consisting of human and animals. A model system of non-linear differential equations for the control of EVD was formulated and the model effective reproduction number () was obtained using the next generation matrix method and used in the stability analysis of the model. Center manifold theorem was used in the bifurcation analysis of the model. Results: The result shows that the stability analysis of the model shows that the EVD – Free Equilibrium is locally asymptotically stable when and EVD - Endemic Equilibrium is locally asymptotically stable when . The model was shown to exhibit a forward bifurcation. Conclusions: Numerical simulations and analysis of the model show that EVD could be effectively controlled and eradicated within a short period of time when vaccine, condom use, quarantine, isolation and treatment drug control measures are implemented together.